Pemanfaatan Teknologi Informasi dalam Meningkatkan Efisiensi Pelayanan Laboratorium untuk Mahasiswa Guna Mendukung Projec Base Learning - Kusumawati, Erlina; Riyadi, Eko Slamet; Hermawanto, Fendi (Jurnal Pengelolaan Laboratorium Pendidikan, 2024)
The utilization of information technology can help improve the efficiency of laboratory services for students in order to support Project Based Learning. The use of information technology allows students to access information related to laboratories and practicum online, register for practicum, and monitor the status of practicum applications that have been made. This can minimize the time and cost required in the laboratory administration process, thus allowing students and laboratory staff to focus more on the main activities in learning. In addition, it can also facilitate the process of collecting, processing, and analyzing the data needed in Project Based Learning, thereby increasing the effectiveness of learning and the quality of project results produced. The research method used is descriptive research by collecting data through observation, interviews, and literature studies. Website development is made using the Laravel framework, and the time required is 2 months. After improving the laboratory service system through a web platform, 90.3% of respondents answered very satisfied and satisfied.